Stigma predicting fertility quality of life among Chinese infertile women undergoing in vitro fertilization-embryo transfer - Xiaoyu Jing; Wei Gu; Xiuli Xu; Chunfang Yan; Peijuan Jiao; Lu Zhang; Xiaomei Li; Xiaoqin Wang; Wenru Wang (Taylor & Francis Group, 2022)
Objective To investigate stigma and fertility quality of life (FertiQoL) and identify predictors of FertiQoL in Chinese infertile women undergoing in vitro fertilization-embryo transfer (IVF-ET). Methods A descriptive correlational design was adopted to investigate the association between stigma and FertiQoL in 588 infertile women undergoing IVF-ET. The personal information questionnaire, Infertility Stigma Scale (ISS) and FertiQoL tool were used to measure study variables. Results The mean scores of ISS and FertiQoL were 62.59 (SD = 21.58) and 63.64 (SD = 13.72), respectively. There were significant differences of ISS scores among participants with different educational level, residence, occupation, religious belief, financial condition, age group, duration of infertility and infertility treatment, while significant differences of the FertiQoL scores were found in participants with different insurance status, determinism of etiology, infertile type, duration of infertility treatment and cycles of IVF-ET. Pearson's correlation analysis showed stigma was negatively correlated with FertiQoL (r = −0.081 to −0.669, p < .05). The self-devaluation (β = −0.290, p < .001), social withdrawal (β = −0.237, p < .001), family stigma (β = −0.217, p < .001) and insurance status (β = 0.066, p=.035) were identified as the significant predictor of FertiQoL accounting for 43.5% of variance. Conclusions The stigma was significantly associated with FertiQoL in infertile women undergoing IVF-ET with higher level of stigma predicting poorer FertiQoL. More psychological support should be provided to infertile women to reduce stigma and improve FertiQoL.